Transgenic pigs to the rescue - Petersen, Björn (eLife, 2018)
Genetically engineered pigs that digest their food better could help to reduce phosphorus and nitrogen pollution.
Keywords: transgenic pigs; Suidae; nitrogen; phosphorus; manure; pollution